Bibliográfia - Polyák, Petra; Dezső, Krisztina; Pálmai, Dóra; Méreg, Martin; Lengvári, István; Varga, Krisztina (Per Aspera ad Astra, 2024)
A Per Aspera ad Astra 2023/1-2. számában közölt tanulmányok bibliográfiája.